Detection of soluble interleukin-2 receptor and soluble intercellular adhesion molecule-1 in the effusion of otitis media with effusion - T. Ganbo; K.-I. Hisamatsu; H. Inoue; K. Kikushima; A. Mizukoshi; Y. Murakami (Mediators of Inflammation)
We measured sIL-2R, TNF-α and sICAM-1 in the sera and middle ear effusions (MEEs) of patients with otitis media with effusion (OME). Although there was no signmcant difference between the sIL-2R levels of the serous and mucoid MEEs, they were significantly higher than serum sIL-2R levels of OME patients and healthy controls. TNF-α levels of the mucoid MEEs were significantly higher than those of the serous type. However, TNF-α was rarely detected in the sera of OME patients or healthy controls. We observed significant differences between the serous and mucoid MEEs with respect to their sICAM-1 levels, which were also higher than serum slCAM-1 levels of OME patients and healthy controls. Our findings suggested that IL-2, TNF-α and ICAM-1 could be significantly involved in the pathogenesis of OME through the cytokine network.